ChemInform Abstract: Discovery and Structure Determination of an Unusual Sulfide Telluride Through an Effective Combination of TEM and Synchrotron Microdiffraction. Issue 42 (October 2015) - Fahrnbauer, Felix; Rosenthal, Tobias; Schmutzler, Tilo; Wagner, Gerald; Vaughan, Gavin B. M.; Wright, Jonathan P.; Oeckler, Oliver
Abstract Polycrystalline Pb8Sb8S15Te5 is prepared by heating stoichiometric amounts of the elements (1.